Poly(N ‐isopropylacrylamide)/polyurethane core–sheath nanofibres by coaxial electrospinning for drug controlled release. (1st May 2016) - Lin, Xiuling; Tang, Dongyan; Lyu, Haitao; Zhang, Qingnan
Abstract : A new type of drug carrier with thermo‐sensitivity is reported. The system consisted of poly( N ‐isopropylacrylamide) (PNIPAAm) and polyurethane (PU) and two kinds of polymer were spun into core–sheath nanofibres without bead defects by coaxial electrospinning technique. Poor soluble nifedipine was used as a model drug to evaluate the release behaviour of drug from nanofibre carriers. Results showed that the diameter and diameter distribution of nanofibres varied with the ratios of the outer flow rate to the inner flow rate. PNIPAAm/PU core–sheath electrospun nanofibres maintained the thermo‐sensitivity of PNIPAAm and the wettability of the electrospun nanofibres could be adjusted effectively by the change of the temperature. In‐vitro release of nifedipine from nanofibre carriers showed that core–sheath electrospun nanofibres as the drug carrier could slow down the release rate of nifedipine compared with that of PNIPAAm/PU composite electrospun nanofibres, and then could effectively achieve the controlled release of nifedipine, avoiding the concentrated release of drug and reduce the toxicity.